Collective forest tenure reform and forest conditions: evidence from the social-ecological system in Southwest China - Li, Wenqing; Chen, Jiahui; Wu, Fengwen; Zhang, Zhiming (Frontiers in Forests and Global Change, 2023)
China’s recent collective forest tenure reform (CFTR) aims to improve forest conditions by devolution of forest management rights from community collectives to individual households. Studies reveal substantial local variation in CFTR implementation, but the ecological effects and underlying mechanism have received little attention. Our study focused on community-managed forests and household-managed forests in four communities located in the mountains of Southwest China. The objective was to investigate the relationship between CFTR and forest conditions at the local scale. We employed a combination of remote sensing technology, field forest observations and socioeconomic surveys to gather data for analysis. The results showed that the forest cover change trends of collective forests and household forests in each community were consistent from 1994 to 2014. There was no significant relationship between CFTR implementation and local-level differences in species diversity and soil fertility in forests. The aboveground biomass of collective forests was significantly higher than that of household forests. Differentiated access and use, low compensation amounts, and loose payment terms jointly affected CFTR’s effectiveness to improve local-scale forest conditions in the study area. Attempts to formalize forest tenure rights must be flexible enough and adapted to the local environment so that changes induced by the CFTR can improve local access to forest resources and its benefits.